Features of polarized Raman spectra for homogeneous and non‐homogeneous compressively strained Ge1−ySny alloys. (10th May 2017) - Perova, T. S.; Kasper, E.; Oehme, M.; Cherevkov, S.; Schulze, J.
Abstract : Raman spectra of homogeneous and non‐homogeneous, compressively strained, Ge‐rich Ge1− y Sn y alloys (with y  < 13%), deposited by molecular beam epitaxy (MBE) techniques using various low‐temperature process conditions, were investigated using polarized micro‐Raman spectroscopy. It is demonstrated that collecting Raman spectra using both polarizations ( z x x z ¯ and z x y z ¯ ) provides more insight into the structural features of GeSn alloys than Raman spectroscopy using an unpolarized probe beam. Acquiring Raman spectra using polarization offers the advantages of enhancing the behaviour of some modes as well as eliminating the overlap of longitudinal optical (LO) modes with unwanted acoustical phonons from the Ge. Raman spectra of samples, grown at extremely low temperatures and identified by X‐ray diffraction as non‐homogeneous, exhibit a lowering of the Ge–Ge peak position, an increase in linewidth and a decrease of the dichroic ratio. Another type of non‐homogeneity appears when the metastable GeSn separates into two phases after obtaining a Sn content‐dependent thickness. Raman microscopy confirmed that the segregates, obtained as a result of phase separation and Sn diffusion to the surface, are of metallic tin origin. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Homogeneous and non‐homogeneous, compressively strained, Ge‐rich Ge1 −  y Sn y alloys (with y  < 13%), deposited by MBE at various low temperatures, were investigated using polarized micro‐Raman spectroscopy. Raman spectra of samples grown by MBE at T  < 100 °C exhibit a lowering of the Ge–Ge peak position, an increase in linewidth and a decrease of the dichroic ratio. This behaviour is significantly different to that observed from samples grown at T  = 160 °C. Raman microscopy also confirmed that surface segregates, obtained as a result of phase separation and Sn diffusion to the surface, are of metallic tin origin.